Electric Field–Controlled Multistep Proton Evolution in HxSrCoO2.5 with Formation of H–H Dimer. Issue 20 (15th August 2019) - Li, Hao‐Bo; Lou, Feng; Wang, Yujia; Zhang, Yang; Zhang, Qinghua; Wu, Dong; Li, Zhuolu; Wang, Meng; Huang, Tongtong; Lyu, Yingjie; Guo, Jingwen; Chen, Tianzhe; et al.
Abstract: Ionic evolution–induced phase transformation can lead to wide ranges of novel material functionalities with promising applications. Here, using the gating voltage during ionic liquid gating as a tuning knob, the brownmillerite SrCoO2.5 is transformed into a series of protonated H x SrCoO2.5 phases with distinct hydrogen contents. The unexpected electron to charge‐neutral doping crossover along with the increase of proton concentration from x = 1 to 2 suggests the formation of exotic charge neutral H–H dimers for higher proton concentration, which is directly visualized at the vacant tetrahedron by scanning transmission electron microscopy and then further supported by first principles calculations. Although the H–H dimers cause no change of the valency of Co 2+ ions, they result in clear enhancement of electronic bandgap and suppression of magnetization through lattice expansion. These results not only reveal a hydrogen chemical state beyond anion and cation within the complex oxides, but also suggest an effective pathway to design functional materials through tunable ionic evolution. Abstract : An ionic liquid gating strategy is proposed, and then a series of H x SrCoO2.5 phases with distinct hydrogen contents is discovered. The unexpected electron to charge‐neutral doping crossover suggests the formation of exotic H–H dimers for higher hydrogen concentration, which is directly visualized at the vacant tetrahedron of the lattice by scanning transmission electron microscopy and supported by theoretical calculations.